The problem of strict image-based inclusion criteria for mechanical thrombectomy – an analysis of stroke patients with an initial low CBV-ASPECTS score. Issue 4 (August 2019) - Schnieder, M; Psychogios, MN; Maier, IL; Tsogkas, I; Schregel, K; Kleinknecht, A; Knauth, M; Bähr, M; Liman, J; Behme, D
Introduction: Endovascular treatment for acute ischaemic stroke with large artery occlusion has become the standard of care. However, the question if a subgroup of patients, with a low cerebral blood volume Alberta Stroke Program Early CT score (CBV-ASPECTS) ≤ 7 should be excluded from endovascular treatment remains open. Therefore; we investigated the difference of outcome between patients who were treated by endovascular treatment vs patients who did not receive endovascular treatment. Methods: We retrospectively analysed our stroke database for all patients who presented within six hours of onset with unfavourable imaging findings and who received endovascular treatment or best medical treatment alone. Unfavourable imaging was defined as a CBV-ASPECTS ≤ 7, which was an exclusion criterion for endovascular treatment at our institution before 2015. Results: From 60 patients with an initial CBV-ASPECTS ≤ 7, 40 received best medical treatment and 20 were treated with endovascular treatment. Arterial hypertension and atrial fibrillation was more present in patients without endovascular treatment, the other baseline characteristics and percentage of patients treated with intravenous recombinant tissue plasminogen activator were not significantly different in both groups. At discharge, 40% of the interventional treated patients had a favourable outcome (eight of 20 (40%) vs six of 40 (15%; p = 0.031). The median values of the National Institute of Health Stroke Score and modified Rankin Scale at discharge were significantly lower in the treated cohort (6.5 (2.5–10.5) vs 16 (9.5–22.5); p = 0.006; 3 (0–5.5) vs 5 (4.5–5.5); p = 0.003). Conclusion: Patients with a CBV-ASPECTS ≤ 7 are likely to benefit from therapy and therefore may not be excluded from endovascular treatment. Further randomised trials are warranted to validate the data.